Transcriptomics Analysis of the Mechanism Underlying the Synthesis of Phenolic Compounds in Fresh-Cut Red Cabbage under Ultrasound Stress - HONG Chen, GUO Lina, ZHANG Xinyan, OUYANG Ningning, WU Ping, MA Haile (Shipin Kexue)
To investigate the molecular mechanism of ultrasound-induced phenolic synthesis in fresh-cut fruits and vegetables, transcriptome sequencing and bioinformatics analyses were carried out on fresh-cut red cabbage washed with and without the assistance of ultrasound at different storage periods. The results showed that at the early storage stage (day 2), 1 142 differentially expressed genes (DEGs) were identified between the control and treatment groups, of which 689 were up-regulated and 453 were down-regulated. At the late storage stage (day 6), 1 166 DEGs were identified, with 480 of them being up-regulated genes and 686 being down-regulated. Bioinformatics analyses revealed that ultrasound significantly modulated metabolic pathways related to reactive oxygen species (ROS) metabolism, energy metabolism, signal transduction, and phenolic biosynthesis. It was further hypothesized that ultrasound washing disrupted ROS homeostasis in fresh-cut red cabbage, promoted ROS production and activated the ROS scavenging system during the initial storage period, thereby inducing phenolic synthesis. Ultrasonic stimulation may induce the expression of genes involved in the conversion of carbohydrate to phenolics by modulating the signal transduction system of fresh-cut red cabbage. Meanwhile, ultrasound washing enabled fresh-cut red cabbage to maintain high levels of energy charge during storage, thus providing energy for this series of reactions. In conclusion, this study provides a theoretical basis for further research on the molecular mechanism of phenolic biosynthesis in fresh-cut fruits and vegetables under ultrasound stress.